Competing magnetic interactions in MnAs studied via thin film domain pattern analysis - Ney, A; Hesjedal, T; Ploog, K (2005)
Manganese arsenide is one of the few ferromagnetic metals that can be grown on semiconductor substrates as a thin film with high structural perfection. The coupled magnetic and structural phase transition around 40°C leads to a variety of different phenomena such as the self-organized stripe formation on GaAs(001) substrates or the anisotropic lattice shrinkage. By investigating the domain pattern in the phase coexistence region we provide experimental evidence that the magnetic order is due to competing ferromagnetic double-exchange and antiferromagnetic direct exchange interactions. This scenario corroborates recent theoretical calculations and may explain the frequently observed angle of 38° in the domain pattern of epitaxial MnAs films. © 2005 The American Physical Society.